x-5x-4-x-3-5x-1-dx- Tinku Tara June 4, 2023 Integration 0 Comments FacebookTweetPin Question Number 167598 by cortano1 last updated on 20/Mar/22 ∫x5x4+x3−5x−1dx=? Answered by MJS_new last updated on 20/Mar/22 ∫x5x4−5x+x3−1dx=∫x(5x+1)(x3−1)dx==∫(25126(5x+1)+118(x−1)−2x+121(x2+x+1)−221(x2+x+1))dx==5126ln∣5x+1∣+118ln∣x−1∣−121ln(x2+x+1)−4363arctan3(2x+1)3+C Terms of Service Privacy Policy Contact: info@tinkutara.com FacebookTweetPin Post navigation Previous Previous post: Question-167593Next Next post: cos-7x-cos-8x-1-2cos-5x-dx- Leave a Reply Cancel replyYour email address will not be published. Required fields are marked *Comment * Name * Save my name, email, and website in this browser for the next time I comment.